Factors Influencing E-Learning Quality from the Perspective of Medical Sciences Students at Alborz University of Medical Sciences - Khedmatizare , Mahsa; Shahmirzad , Nilufar; Nekouei , Mehrad; Sanjari, Elaheh; Aghabarary, Maryam (Advances in Nursing & Midwifery, 2025)
Abstract Introduction: Given the widespread use of e-learning during the COVID-19 pandemic and the post-pandemic period—particularly in the critical field of medical sciences—examining students’ perspectives on factors influencing e-learning quality is essential. The present study was conducted to investigate medical sciences students’ perspectives on the factors affecting e-learning quality. Methods: In this descriptive cross-sectional study, 854 medical sciences students at Alborz University of Medical Sciences, Karaj, Iran, were selected using convenience sampling between January and May 2022. The data collection instrument was a researcher-developed questionnaire comprising two sections: demographic information and factors influencing e-learning quality. After data collection, the data were analyzed using SPSS version 20, employing descriptive and inferential statistics at the P ≤ 0.05 significance level. Results: The mean score for instructor-related factors was 141.64 ± 19.41 (range: 35–175); for factors related to the educational content delivered, it was 55.32 ± 7.84 (range: 13–65); and for factors related to facilities, equipment, and infrastructure, it was 26.52 ± 3.63 (range: 6–30). Based on the results of the Friedman test, the highest-ranked domain was "factors related to facilities, equipment, and infrastructure". Among all dimensions, the items with the highest mean scores were as follows: teaching skills, mastery of the subject matter, ability to integrate theoretical and clinical content during instruction to facilitate better understanding, clear presentation of key and practical points in the instructional content, alignment between the amount of educational content and the learning objectives, scientific accuracy of the content, and inclusion of up-to-date material, the functioning microphone and uninterrupted audio, adequate internet speed, and availability of online class recording. Conclusions: The development of adequate technical infrastructure, targeted investment, and the establishment of clear standards for evaluating learners’ performance are essential for the effective utilization of e-learning. It is recommended that educational authorities and policymakers focus their efforts on enhancing the infrastructure of educational platforms and improving internet speed and quality. Additionally, organizing training workshops for faculty members on the principles of designing and conducting online classes, as well as producing standard electronic content, can contribute to improving instructors’ teaching competencies and better addressing students’ learning needs.